2002
DOI: 10.1177/0145445502026004005
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Physical Guidance as Reinforcement for Noncompliance

Abstract: Physical guidance is a strategy commonly used for noncompliance. In two experiments, we evaluated reinforcing effects of physical guidance. Experiment 1 include three individuals with developmental disabilities who were noncompliant with tasks. Anecdotal observations indicated physical contact was highly reinforcing, and a functional analysis identified attention as a reinforcer for problem behavior. Two conditions compared physical guidance following noncompliance and no physical guidance following noncomplia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Thus, the purpose of the current study was to describe a method for evaluating the relative contributions of escape and attention in the maintenance of noncompliance. Our procedures were similar to the functional analysis described by Kern, Delaney, Hilt, Bailin, and Elliot (2002), which was designed to evaluate noncompliance of an adult woman and adolescent boy who had been diagnosed with developmental disabilities.…”
mentioning
confidence: 99%
“…Thus, the purpose of the current study was to describe a method for evaluating the relative contributions of escape and attention in the maintenance of noncompliance. Our procedures were similar to the functional analysis described by Kern, Delaney, Hilt, Bailin, and Elliot (2002), which was designed to evaluate noncompliance of an adult woman and adolescent boy who had been diagnosed with developmental disabilities.…”
mentioning
confidence: 99%
“…Iwata et al () demonstrated that extinction procedures that matched the function of behavior effectively reduced the target behavior whereas mismatched extinction procedures did not. A handful of other studies have produced similar results (Brown et al, ; Kern, Delaney, Hilt, Bailin, & Elliot, ; Kuhn, DeLeon, Fisher, & Wilke, ; Richman, Wacker, Asmus, & Casey, ). Although predictive accuracy of the function of problem behavior has not been formally quantified using the methods described in the current study, we can characterize it as PBM in light of the extensive body of evidence supporting function‐based interventions and the status of this approach as reflecting best practice.…”
Section: Discussionmentioning
confidence: 53%
“…The physical guide served as a positive reinforcer of child's noncompliance behaviors and increased their occurrence. According to Kern et al (2002), physical guide was recommended only when noncompliance's behavior served as an escape function.…”
Section: Discussionmentioning
confidence: 99%